2002
DOI: 10.1111/j.0956-7976.2002.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's Use of Landmarks: Implications for Modularity Theory

Abstract: Previous studies have shown that disoriented children use the geometric features of the environment to reorient, but the results have not consistently demonstrated whether children can combine such information with landmark information. Results indicating that they cannot suggest the existence of a geometric module for reorientation. However results indicating that children can use geometric information in combination with landmark information challenge the modularity interpretation. An uncontrolled variable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
202
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(218 citation statements)
references
References 16 publications
13
202
2
1
Order By: Relevance
“…The first theory builds on the classic results by arguing that reorientation is mediated by an encapsulated cognitive module (41) that specifies a navigator's position and orientation relative to the geometric structure of the environment but is insensitive to nongeometric features (5-7). The second theory argues that a range of environmental cues, including both geometry and nongeometric features, can guide spatial reorientation (9,10,42) and that the combination of cues used in any given situation can vary depending on their salience and reliability. Although our results might seem at first glance to fit more closely with the first view insofar as we postulate the operation of independent mechanisms, one of which is especially sensitive to geometry, it is important to note that our argument does not require that these two mechanisms be modular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first theory builds on the classic results by arguing that reorientation is mediated by an encapsulated cognitive module (41) that specifies a navigator's position and orientation relative to the geometric structure of the environment but is insensitive to nongeometric features (5-7). The second theory argues that a range of environmental cues, including both geometry and nongeometric features, can guide spatial reorientation (9,10,42) and that the combination of cues used in any given situation can vary depending on their salience and reliability. Although our results might seem at first glance to fit more closely with the first view insofar as we postulate the operation of independent mechanisms, one of which is especially sensitive to geometry, it is important to note that our argument does not require that these two mechanisms be modular.…”
Section: Discussionmentioning
confidence: 99%
“…The animals will often ignore other orienting cues such as odors, visual patterns, and wall color, even when these cues provide polarizing information that could potentially resolve the geometric ambiguity (6,8). Although the exclusive reliance on geometric cues is not found under all circumstances (9,10), it has been observed in a large number of studies.…”
mentioning
confidence: 99%
“…in large rooms, see Learmonth et al 2002Learmonth et al , 2001Nadel and Hupbach 2006; see also Sovrano et al 2005Sovrano et al , 2007Vallortigara et al 2005a;Vallortigara and Sovrano 2002;Sovrano and Vallortigara 2006;Chiandetti et al 2007 for evidences in other species). Nonetheless, a weak version of modularity has been claimed on the basis of the evidence for a speciWc neural mechanism (likely located in the hippocampus) dedicated to the treatment of geometric information (Bingman et al 2006;Vargas et al 2004b;Vallortigara et al 2004;Tommasi et al 2003;Vallortigara in press).…”
Section: Introductionmentioning
confidence: 98%
“…The authors suggested that the main procedural difference between their study and that of Hermer and Spelke was the size of the experimental room. A follow-up study by Learmonth et al (2002) directly compared the use of geometric and featural cues by young children (36 -59 months) within two different room sizes. One of the rooms was the same size as used by Hermer and Spelke and the other was the same size as the room used by Learmonth et al (2001).…”
mentioning
confidence: 99%